2017
DOI: 10.1038/srep40853
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal pesticide doses negatively affect survival and the cellular responses in American foulbrood-infected honeybee larvae

Abstract: Disclosing interactions between pesticides and bee infections is of most interest to understand challenges that pollinators are facing and to which extent bee health is compromised. Here, we address the individual and combined effect that three different pesticides (dimethoate, clothianidin and fluvalinate) and an American foulbrood (AFB) infection have on mortality and the cellular immune response of honeybee larvae. We demonstrate for the first time a synergistic interaction when larvae are exposed to sublet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 67 publications
5
31
0
1
Order By: Relevance
“…The results demonstrated here in bumblebees are congruent with the outcomes of prior studies investigating interactions between neonicotinoid exposure and immunity in honeybees (Alaux et al., ; Di Prisco et al., ; Brandt et al., ; López et al., ). This is not a trivial extension, as honeybees and bumblebees, while both highly susceptible, have been suggested to differ in their detoxification of neonicotinoids (Cresswell, Robert, Florance, & Smirnoff, ), and neonicotinoid exposure and parasite stress has been shown to have differential effects in the two groups of bees (Piiroinen & Goulson, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results demonstrated here in bumblebees are congruent with the outcomes of prior studies investigating interactions between neonicotinoid exposure and immunity in honeybees (Alaux et al., ; Di Prisco et al., ; Brandt et al., ; López et al., ). This is not a trivial extension, as honeybees and bumblebees, while both highly susceptible, have been suggested to differ in their detoxification of neonicotinoids (Cresswell, Robert, Florance, & Smirnoff, ), and neonicotinoid exposure and parasite stress has been shown to have differential effects in the two groups of bees (Piiroinen & Goulson, ).…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that neonicotinoid exposure increases pathogen spore load and mortality in honeybees infected with the microsporidian Nosema ceranae (Alaux et al., ; Vidau et al., ; Pettis, van Engelsdorp, Johnson, & Dively, ; Retschnig, Neumann, & Williams, ). Similar results have been shown for honeybee viral (Di Prisco et al., ; Doublet, Labarussias, de Miranda, Moritz, & Paxton, ) and bacterial infection (López et al., ). In bumblebees, exposure to clothianidin and thiomethoxam and a trypanosome parasite reduce mother queen longevity in a greater than additive manner (Fauser‐Misslin et al., ), although effects on overwintering were less than additive, with strong early pesticide exposure effects masking later parasite effects (Fauser et al., ).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, a second larval cell type, resembling those described as L5-2 by Negri et al (2014b), were also observed though they were not encountered during cytospin transect counting, indicating that they are either rare or not easily distinguished using the methods described here. It is possible that the cytospin method we employed resulted in the loss or degradation of cell types observed in other works (e.g., López et al 2014López et al , 2017. Alternatively, additional cell types may be inducible upon infection or wounding.…”
Section: Discussionmentioning
confidence: 74%
“…There is clear evidence that bee larvae reared in treatment combs containing insecticide residues experience delayed development . Reduced survival and weight loss are the main indicators of the effects of insecticides on bee larvae in the literature . Several studies have even confirmed that insecticide toxicity occurs at lower exposure rates to larvae compared to adult bees …”
Section: Introductionmentioning
confidence: 99%